PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE LEARNING CELL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 1 BATANG KAPAS - Fitri, Sherly Adrila; Anggraini, Villia; Pratiwi, Merina (Pendidikan Matematika, 2013)
This research of background is the important of mathematics concept comprehension studentâs, and the unusually of studentâs discuss with their friend. This research to determine how indicator of studentâs concept comprehension about studentâs mathematics concept by using active learning strategy type The Learning Cell, to determine Â what is mathematics concept comprehension of studentâs by using active learning strategy type The Learning Cell better than studentâs mathematics concept comprehension using conventional. The kind of this research is experiment, by using random sampling research. The formulation is all of IX SMPN 1 Batang Kapas and the sample is IX.5 as experiment class and IX.4 as control class. The instrument that is used in this research are quiz and test. The function of quiz is to see the development of studentâs mathematics concept comprehension indicator an the test used to see mathematics concept comprehension that consist of seven items in essay form with reability 0,98. Based on the quantitative analysis that is done on normality test by using MINITABâS program we can get p-value 0,713 for experiment class and p-value 0,909 for control class, soo the hypothesis using t test by significant 0,05. Based on description of data and hypothesis test, can be conclude that the studentâs mathematics by using active learning type The Learning Cell is better than studentâs mathematics concept comprehension by using conventional learning studentâs.